Overconfidence and gender gaps in career outcomes: Insights from a promotion signaling model - Spencer Bastani; Thomas Giebe; Oliver Gürtler (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
Gender differences in overconfidence are well documented in the empirical literature, but their impact on labor market outcomes remains underexplored. We provide new insights into how behavioral biases interact with career dynamics by presenting a theoretical analysis of how men's relatively higher overconfidence shapes gender differences in the labor market. Using a promotion-signaling model with competitive work incentives in which wages are endogenously determined, we show that overconfident workers exert more effort, are more likely to be promoted, and ultimately earn higher wages across job levels despite having lower expected ability conditional on promotion. The higher effort not only increases their chances of promotion, but also contributes to human capital accumulation through learning-by-doing, leading to higher productivity. However, overconfidence can be a double-edged sword: while it can lead to higher promotions and wages (serving as a "self-serving bias"), it also imposes higher effort costs and discourages peers, which can make it self-defeating in certain contexts.
Keywords: C72; D91; J16; J24; M51; M52; 330; overconfidence; promotion; competition; gender gap; tournament; theory